TAFSIR AYAT AL-QUR'AN TEMA KEPERAWATAN, KEBIDANAN DAN FAKTA ILMIAHNYA - Setiawan, Iwan (Universitas 'Aisyiyah Yogyakarta, 2017)
Abstract: The Qur'an is the source of all sources in understanding this life. In the world of health was discussed in the Qur'an, began about the sperm to the moment people become senile. Of course we as Muslims need to understand and study it with the latest scientific findings. So we are more mantab over Islam that became our religion. This research includes research of Library Research by taking reference books that fit with the theme discussed. In this study will be collected verses Al-Qur'an theme of nursing and midwifery following interpretation of these verses and scientific facts. Conclusion: The Qur'an is the ocean of knowledge. So studying the Koran and being associated with themes in Nursing and Midwifery is a necessity.Keywords: verses of al-quran, nursing and obstetrics, interpretation of health verses, scientific facts